Legal Issues Concerning of Data Security and Privacy in Automated Income Tax Systems in Nigeria - Aidonojie, Paul Atagamen; Majekodunmi, Toyin Afolabi; Eregbuonye, Obieshi; Ogbemudia, Isaac Ottah (Hang Tuah Law Journal, 2024)
The adoption of automated income tax systems in Nigeria has ushered in a new era of efficiency and transparency, offering promising prospects for streamlined tax administration. However, the absence of comprehensive data protection legislation and potential cybersecurity threats pose significant challenges. The legal landscape surrounding data security and privacy in the context of automated tax systems necessitating an in-depth exploration of this study. This study aims to analyze the prospects and legal challenges associated with data security and privacy in the implementation of automated income tax systems in Nigeria. The study employs a multi-faceted methodology, combining a thorough review of existing literature and an analysis of relevant legal frameworks. Additionally, 303 questionnaires were distributed to respondents to ascertain insights concerning the prospect of automated income tax and cybersecurity measures in place concerning data security and privacy. The study found that there are several prospects associated with automated income tax systems, including increased efficiency, transparency, and enhanced revenue collection. However, legal challenges are identified, such as the lack of comprehensive data privacy legislation, cybersecurity threats, and control. The study therefore concludes that, while automated income tax systems offer significant benefits, addressing the legal challenges is paramount for their successful implementation. The study recommends the urgent enactment of comprehensive data protection legislation, the implementation of robust cybersecurity measures, and increased public awareness programs. Additionally, guidelines for international data transfer should be established to ensure the privacy and security of taxpayer information.